COSMOPOLITANISM AND CULTURAL DIVERSITY IN “THE PHYSISCIAN” BY NOAH GORDON (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The main idea of this article  is to explore how cosmopolitanism, cultural diversity, and religious tolerance are shown in Noah Gordon’s The Physician. The dissertation looks at how the main character, Rob Cole, grows both as a person and as a doctor by learning from different cultures—Christian, Jewish, and Muslim. It argues that cosmopolitanism helps people develop and also makes societies stronger by encouraging cooperation and understanding. The novel shows that being open to new ideas and learning from others can lead to personal and professional growth.Cosmopolitanism is very important in today’s world. We live in a globalized time, where people from different cultures are always interacting because of travel, migration, and technology. Cosmopolitanism teaches us to value tolerance, empathy, and respect for diversity, which are important for living peacefully in multicultural societies. For example, in many big cities today, people from different backgrounds live together. Learning about cosmopolitanism helps us understand how to build communities where everyone can live in harmony and work together.